2015
DOI: 10.54718/xuls8249
|View full text |Cite
|
Sign up to set email alerts
|

College Students’ Perceptions and Practices Towards Environmentally Friendly Clothing: A Comparison and Exploratory Study

Abstract: Despite the growing interest of environmentally friendly clothing (EFC), there have been discrepancies among customers in defining EFC. The purposes of this study were to assess the participants’ environmental orientation and environmental knowledge toward EFC, to compare them in terms of college major and gender and identify relationships between orientation and knowledge, and to acquire the current perceptions and practices toward EFC. The revised New Environmental Paradigm scale (NEP) with 15 items, the Env… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…An examination of NEP-R summed scores showed no significant difference between students enrolled in different colleges and departments. Müderrisoglu and Altanlar (2011) and Nam and Chatmon (2015) previously found that a student's academic major did not influence environmental attitudes. However, Kuo and Jackson (2014) found undergraduate students pursuing engineering majors measured lower in endorsing pro-environmental worldviews than non-engineering majors.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…An examination of NEP-R summed scores showed no significant difference between students enrolled in different colleges and departments. Müderrisoglu and Altanlar (2011) and Nam and Chatmon (2015) previously found that a student's academic major did not influence environmental attitudes. However, Kuo and Jackson (2014) found undergraduate students pursuing engineering majors measured lower in endorsing pro-environmental worldviews than non-engineering majors.…”
Section: Discussionmentioning
confidence: 94%
“…Research Question 1 NEP-R items and summed scores were calculated and summarized to answer research question one; what are the environmental worldviews for students at a public four-year university located in the Southwest United States? Even-numbered NEP-R items were reversed coded and interpreted as disagreement indicating a pro-environmental orientation (Dunlap et al, 2000;Nam & Chatmon, 2015). The overall NEP-R index (M = 3.55, SD = 0.65) showed that participants measured toward a pro-environmental orientation using the item score categories ranging from 1.00 to 2.99 as a negative attitude toward the environment and a mean score ranging from 3.00 to 5.00 indicating a positive attitude toward the environment (Erkal et al, 2012).…”
Section: Resultsmentioning
confidence: 99%